Spring book stopper - Zamani, Arnieza Zanira; Mohd Johari, Nur Afifah; Ahmad, Azree (Universiti Teknologi MARA, Kedah, 2017)
The spring book stopper is design to assist users and library staff in retrieving and reshelving books from the shelve. Common problems that exist pertaining to libray book shelve is that books arrangements are usually not in order due to continuous retrieval and shelving by users thus creating a gap between books on the shelve. Such gap exist because the book divider is not intact to the shelve and could easily be misplaced or moved from its intended position thus reflects the arrangement of books on that shelve. Based on the design, it will be easy for users to browse and use the books from the shelve as the book divider or stopper works automatically to close these gaps. An improvement to the existing book divider where a movable book divider is built into the existing shelve unit. Its design considers elements of flexibility that benefits both library users and library staffs